2014
DOI: 10.1080/17480930.2014.932940
|View full text |Cite
|
Sign up to set email alerts
|

Determination of suitable plant species for reclamation at an abandoned coal mine area

Abstract: This study was conducted to determine suitable plant species for reclamation of an abandoned coal mine area at Ovacik village within the borders of Yaprakli town in the province of Cankiri, Turkey. The paper comprises three basic parts: (i) sampling and analyses of several chemical-physical properties of the soil; (ii) sampling and identification of the natural plant species; and (iii) determination of topographic features of the study area by spatial analysis tools. Soil samples were taken from 0 to 30 cm dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Issues of the landscape-geochemical exploration allowing quantitative assessment and delivery of practical advice on how to improve the ecological situation have been thoroughly examined, and a significant amount of environmental data are collected describing the impact of mining and processing industries, as well as practicable methods for rehabilitation of lands affected by the production of building materials among other things (Alguacil et al, 2006;Androkhanov et al, 2019;Doley et al, 2012;Kuter et al, 2014;Moreno-de las Heras, 2008;Pivnyak et al, 2011;Timofeev et al, 2014). However, the available assessment data obtained in the course of studies of territories affected by cement crude material mining include only concrete cases and contain no recommendations on how to handle environmental damage in other conditions beyond the limits of such cases.…”
Section: Disturbance and Reclamation Of A Mining Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Issues of the landscape-geochemical exploration allowing quantitative assessment and delivery of practical advice on how to improve the ecological situation have been thoroughly examined, and a significant amount of environmental data are collected describing the impact of mining and processing industries, as well as practicable methods for rehabilitation of lands affected by the production of building materials among other things (Alguacil et al, 2006;Androkhanov et al, 2019;Doley et al, 2012;Kuter et al, 2014;Moreno-de las Heras, 2008;Pivnyak et al, 2011;Timofeev et al, 2014). However, the available assessment data obtained in the course of studies of territories affected by cement crude material mining include only concrete cases and contain no recommendations on how to handle environmental damage in other conditions beyond the limits of such cases.…”
Section: Disturbance and Reclamation Of A Mining Landscapementioning
confidence: 99%
“…Low-height and creeping juniper species are among the most common plants on rocky slopes and rocks in the region. Cade is photophilous, drought tolerant, and unpretentious to soil conditions (Alguacil et al, 2006;Caravaca et al, 2006;Kuter et al, 2014). Smoke tree, Cotinus coggygria Scop.…”
Section: Biological Reclamationmentioning
confidence: 99%
“…Continuous mining practices leading to deformation, strata movement, and subsidence. These can alter the physical properties of soils and result in their nitrogen leaching into soils as nitrate (Kuter et al 2014;Masilionytė et al 2014;Endale et al 2017). Such increasing trend of NO3levels in coal mining areas have been demonstrated in Elk Valley and West Line Creek, Canada, where rising concentrations (from 6.5 mg/l in 1994 to 38.5 mg/l NO3in 2006) were correlated to increasing volumes of coal mine waste rock (Mahmood et al 2017;Hendry et al 2018).…”
Section: Introductionmentioning
confidence: 97%
“…These in uences can be restored through land reclamation and ecological restoration measures, which have been proved to be an effective way to restore the destructive environment in mining areas (Heras et al 2011, Krümmelbein and Raab 2012, Mukhopadhyay et al 2013, Qiu et al 2019, Xiao et al 2019). Land subsidence, as one of the signi cant in uences by underground coal mining, will not only change soil quality but also cause many other eco-environmental problems (Huang et al 2014, Kuter et al 2014, Qiu et al 2019, Wang et al 2017, Yang et al 2016, Yang et al 2018, Yang et al 2019). Statistics showed that 10,000 tons raw coal production would averagely lead to 0.2 hectares subsided lands in China (Bian et al 2010).…”
Section: Introductionmentioning
confidence: 99%